Campuran Fly Ash dan Petrasoil dalam Peningkatan Daya Dukung Tanah - Indrayani -; Andi Herius; Sudarmadji -; Ahmad Mirza; Daiyan Saputra; Al Muhammad Fadil (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2020)
As an effort to improve the subgrade, some construction projects use petrasoil material to increase the carrying capacity of the soil, for example in the construction of the "Improvement of the Tabarfane-Hokmar Soil Road (Chemical Petrasoil)” in Aru sub-district. Previous research on increasing the carrying capacity of the soil have been done using petrasoil, but the results indicated no soil carrying-capacity increase. On the contrary, another study successfully used fly ash on swamps to increase the soil carrying-capacity. Based on these two studies, the current research combined the two additives, namely, fly ash and petrasoil, to increase soil carrying-capacity and get an optimal additive composition. Some tests have been carried out, i.e. the index properties test, compaction test, and CBR test using AASHTO and ASTM standards. Fly ash mixtures were prepared in several composition percentages, i.e. 0%, 10%, 15%, 20%, while the mixture of petrasoil and water is 1 kg: 1000 liters. The results showed that there was an increase in soil bearing capacity based on the largest CBR value in the variation of mixed soil with petrasoil and fly ash by 20% which is equal to 19.7% of the CBR value of original soil without additives.